Dinamika Umat di Masa Pandemi COVID 19: Lingkup Wilayah dan Keterlibatan Umat di Gereja - Cahyono, Ratna Tri; Adi, Alvarado Putra (Felicitas, 2021)
The Covid-19 pandemic is a reality faced by all humans in the last two years. This pandemic made many fields undergo radical changes and gave rise to many new habits and new cultures. Although the covid pandemic is still running, the involvement of the people in environmental and church activities is still going well. This made the aspirations of the Ardas diocese of Surabaya begin to penetrate the people. Seeing that there is still a spirit of the people for activities, both in the environment and the Church, it is necessary to pay attention to all the faithful.